Pengganti Kehamilan Lintas Negara dan Kekosongan Hukum dalam Hukum Keluarga Indonesia: Perlindungan Status Anak dalam Perspektif Hukum Islam, Hukum Perdata Internasional, dan Hak Anak - Intan Pelangi; Adhimaz Kondang Pribadi (Universitas Muhammadiyah Metro, 2026)
Cross border surrogacy presents complex legal issues in Indonesia because no specific rule determines the legal status of a child born through a surrogacy arrangement abroad, while Article 58 of Law Number 17 of 2023 permits assisted reproduction only when an embryo created from a married couple's own gametes is implanted in the wife from whom the ovum originated. Existing discussions commonly separate the permissibility of surrogacy, nasab (lineage), foreign parentage, citizenship, and children's rights. The research gap lies in the absence of an integrated Indonesian framework that distinguishes the invalidity of the adult arrangement from the continuity of the child's legal status. This normative legal study applies statutory, conceptual, case, and functional comparative approaches, comparing Indonesia with France, the United Kingdom, and India. The study identifies four dimensions of legal vacuum: substantive parentage rules, conflict of laws rules, judicial and registration procedures, and inter institutional coordination. Its novelty is a two-track status separation model: an ex ante track that retains prohibition or strict restriction of surrogacy, and an ex post track that guarantees birth registration, nationality assessment, judicial determination of parentage, non-abandonment, maintenance, and access to origin information according to the child's best interests. Thus, protecting the child does not legalise surrogacy; it prevents the rejection of adult conduct from becoming the legal abandonment of the child.